Mutualistik Organisasi Dan Produktivistas Kerja Dosen Dalam Perspektif Tafsir Tematik - As’aril Muhajir (Qolamuna : Jurnal Studi Islam, 2019)
Abstract The article describes an interpretation of Al-Qur’an with a thematic approach in understanding mutualistic of college organization and lectures’ productivity. Al-Qur’an frequently states the word ‘amal’ in both singular and plural forms (a’maal). The word is derived from a verb (fi’il) “ ???????? – ?????? ” work or doing something. Words like “jahada”, “kasaba”, and sa’aa” have similar meaning. Operational productivity is eficiency of resource utilization in creating an output. In philosophical term, productivity, meanwhile, is a mental state in viewing point that today’s output is better than yesterday’s and tomorrow’s is better than today’s. Keywords : Organization, Lectures’ productivity.